Urological issues in cyclists. (March 2022) - Peacock, J; Cobley, J; Patel, B
Cycle use has grown rapidly over the last few years in the UK. British Cycling membership has increased threefold since the 2012 Olympic and Paralympic Games, and this is likely to rise in the wake of the Coronavirus pandemic. As urologists, day-to-day encounters with cyclists are commonplace, who may present with acute traumatic injuries or chronic overuse injuries. The aim of this literature review was to evaluate the effect of cycling on conditions presenting to the urology clinic, in particular those of raised prostate-specific antigen (PSA), haematuria and soft-tissue lesions ('cyclist nodules'). Furthermore, the review aimed to summarize the relationship between cycling and pudendal nerve entrapment (PNE) syndromes. A PubMed search of the literature on cycling and genitourinary disorders was performed. The literature suggests no significant change in PSA levels after a bout of cycling. Age appears to have no effect on the change in PSA experienced following a bout of cycling, in particular when comparing those <50 years of age to those >50 years of age. Haematuria appears to be rare with cycling but has been described, even with stationary bike riding. It is imperative to exclude coexisting urinary-tract pathological conditions, and cycling-induced haematuria should always be considered a diagnosis of exclusion. Perineal nodular induration ('cyclist nodules') is a rare condition, related to pressure and repetitive micro-trauma between the perineum and saddle. Pudendal Nerve Entrapment (PNE) represents the most common bicycling-associated urogenital complaint. Numbness in the perineum, penis, scrotum or buttocks—'genital numbness'—is the most common and most recognized symptom of pudendal compression. Despite several studies demonstrating a link between elite cyclists and erectile dysfunction, for the average cyclist riding may actually have a protective effect on sexual function.